ERGONOMIC POSTURE ASSESSMENT OF BUTCHERS: A SMALL ENTERPRISE STUDY IN MALAYSIA FOOD INDUSTRY (Jurnal Teknologi (Sciences & Engineering), 2019)
The development of small and medium-sized enterprises (SMEs) is crucial for improving the economy of a rural area. However, this can cause working posture problems, such as musculoskeletal disorders (MSDs) and cumulative trauma disorders (CTDs). This is especially true for butchers, who work in SMEs that still depend on manual handling processes without standard operating procedures. Posture analysis evaluations using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) tools have been used to analyse the working postures of butchers working in SMEs. The aim of this study was to identify butchers’ risks of working posture problems, and to propose an ergonomic workstation designed to reduce MSDs and CTDs. This study was focused on smoked meat preparation. The butchers there spend 5–8 hours a day cutting and trimming meat. The assessment was conducted using RULA and REBA worksheets. The RULA score for the meat trimming process was 7, with a score of 6 for the meat cutting process. As for REBA, the score was 5 for both the meat trimming and meat cutting processes. Based on these scores, the butchers were at higher risks for MSDs and CTDs. Therefore, a new ergonomic workstation design was proposed based on the principles of motion economy.